The Impact of Islamic Finance on Carbon Emissions: Lessons from OIC Countries - Irfany, Mohammad Iqbal; Syam, Muhammad Ilham Nurhuda; Haq, Daffa Aqomal (International Journal of Energy Economics and Policy, 2024)
Environmental degradation especially the spread of emissions per capita in OIC countries has increase very rapidly with one of the factors being sharia bank financing. This study aims to know the financing of sharia banking and the other common factors in influencing emissions per capita in OIC countries. The method that will be used is panel data analysis with the Generalized Least Square (GLS) weighting model Fixed Effect Model (FEM). The results of this study indicate that Islamic bank financing, real GDP per capita, and trade openness have a positive and significant effect on emissions per capita. Then from the results of this study indicate that urbanization has a negative but it’s not significant effect on emissions per capita. The results of this study can be used as a basis for sustainability policies in the government and company regulations such as the application of the concept of green industry and the development of clean and environmentally friendly technologies and sharia banking in OIC countries can provide sustainable financing so that the financing provided is not only profit-oriented but also realizes green financing for the community and companies in general.